2014
DOI: 10.1371/journal.pone.0093114
|View full text |Cite
|
Sign up to set email alerts
|

Does Dexmedetomidine as a Neuraxial Adjuvant Facilitate Better Anesthesia and Analgesia? A Systematic Review and Meta-Analysis

Abstract: BackgroundNeuraxial application of dexmedetomidine (DEX) as adjuvant analgesic has been invetigated in some randomized controlled trials (RCTs) but not been approved because of the inconsistency of efficacy and safety in these RCTs. We performed this meta-analysis to access the efficacy and safety of neuraxial DEX as local anaesthetic (LA) adjuvant.MethodsWe searched PubMed, PsycINFO, Scopus, EMBASE, and CENTRAL databases from inception to June 2013 for RCTs that investigated the analgesia efficacy and safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 47 publications
8
68
1
2
Order By: Relevance
“…Dexmedetomidine is a potent and highly selective a 2 -adrenoceptor agonist with sympatholytic, sedative, amnestic, 6 and analgesic 7 properties. Clinical researchers have already studied the administration of dexmedetomidine to prevent shivering.…”
mentioning
confidence: 99%
“…Dexmedetomidine is a potent and highly selective a 2 -adrenoceptor agonist with sympatholytic, sedative, amnestic, 6 and analgesic 7 properties. Clinical researchers have already studied the administration of dexmedetomidine to prevent shivering.…”
mentioning
confidence: 99%
“…Neuraxial dexmedetomidine was associated with good sedation scores and lower analgesic requirements and stable into-operative hemodynamics. 22 Crews et al found in their study that the use of continuous levobupoivacaine in addition to morphine via a thoracic epidural catheter produced an excellent segmental sensory block and analgesia. 23 All the above studies showed that dexmedetomidine was a better adjuvant to levobupivacaine in epidural anaesthesia.…”
Section: Discussionmentioning
confidence: 97%
“…Neuraxial dexmedetomidine was associated with good sedation scores and lower analgesic requirements and stable into-operative hemodynamics. [22] Crews et al found in their study that the use of continuous levobupoivacaine in addition to morphine via a thoracic epidural catheter produced a excellent segmental sensory block and analgesia. [23] All the above studies showed that dexmedetomidine was a better adjuvant to levobupivacaine in epidural anaesthesia.…”
Section: Discussionmentioning
confidence: 98%